Effect of Play-Based Occupational Therapy on Hand Function of Children with Cerebral Palsy: A Quasi-Experimental Study - Hussein, Zainab Abd al Ameer; Shawq, Adraa Hussein (Iraqi National Journal of Nursing Specialties, 2026)
Objective(s): This study aims to improve hand function in children with cerebral palsy through using of play therapy methods: clay, beads, and sand, and find most effect method. Methods: A quasi- experimental study employed pre-test and posttest design with control group. It was conducted at the Centre of Medical Rehabilitation and Arthritis in Baghdad city, at the period November 25th, 2024, to February 13th, 2025. A non-probable sample of 64 children with cerebral palsy was selected by non-random sampling method, they were distributed into one control group and three intervention groups. Both groups continue with their routine care in the center, and only the intervention group expose to play therapy intervention. The Box and Block Test was used to assess children`s hand function before and after play intervention. The data was analyzed by using descriptive and inferential statistics by SPSS program. Results: The result showed no significant differences in the means score of hand function in the both groups before play intervention. However, after the intervention a significant difference was clear in sand and clay intervention groups. The statistics showed clay therapy was most effective at, P value ≤ 0.05. Conclusion: Nursing interventions incorporating play therapy methods are effective in improving hand function in children with CP. These methods consider child-friendly and engaging valuable methods. Recommendations: A cohort study is recommended to assess the long-term effects of play interventions. Pediatric nurses need to integrate these play-based therapies and family’s participation to enhance motor skills of hand function in children with CP.